Analyzing the needs of teaching and learning content low carbon education at Junior High School in Indonesia - Mutia Sri Rahayu; Indriyani Rachman; Anna Permanasari (EDUSAINS, 2025)
This study aims to identify the needs in the development of teaching materials on low carbon education, which is still rarely delivered at the VII grade secondary school level. This research uses the Mix Method. Quantitative data collection with a total of 100 respondents located in Bogor regency in the 2024/2025 academic year using assessment questions on the level of knowledge, low carbon competencies, and environmental care attitude questionnaire. Meanwhile, qualitative data were generated from observations of climate resilience based on the geographical location of the education unit. The results of this study show that students still need improvement in knowledge, low carbon competency, and environmental care attitude. The climate resilience analysis shows that the school conditions have the potential to implement learning that raises environmental issues to be used as topics in learning, and the use of social media. Therefore, the need for the development of teaching materials includes learning that contains videos or images, case studies with local issues, accompanied by group assignments that integrate social media as a medium for campaigns to protect the environment, so that it accommodates learning that forms an attitude of environmental care.